1993
DOI: 10.1007/bf00180262
|View full text |Cite
|
Sign up to set email alerts
|

The double ??5.6 helix of gramicidin a predominates in unsaturated lipid membranes

Abstract: The structure of the channel-forming polypeptide gramicidin A (GA) incorporated into phosphatidyl-choline (PC) liposomes has been studied as a function of the degree of unsaturation of the acyl chains of PC. The initial conformational state of GA in reconstituted bilayers is determined by the solvent in which the peptide and the lipid are initially co-dissolved, whereas the equilibrium conformational state (after heat incubation) is affected by the lipid structure rather than by the nature of the solvent. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 36 publications
6
60
2
Order By: Relevance
“…Despite recent claims to the contrary, (13) it is very clear that the principal conducting form of gramicidin is the HD. (15,16) Only under limited conditions (17,18,19) do DHs form conducting structures. Since gramicidin does not have any polar or hydrophilic amino acids, it forms ion-conducting pathways from the carbonyl oxygens of its polypeptide backbones.…”
Section: Gramicidin Ion Channelsmentioning
confidence: 98%
“…Despite recent claims to the contrary, (13) it is very clear that the principal conducting form of gramicidin is the HD. (15,16) Only under limited conditions (17,18,19) do DHs form conducting structures. Since gramicidin does not have any polar or hydrophilic amino acids, it forms ion-conducting pathways from the carbonyl oxygens of its polypeptide backbones.…”
Section: Gramicidin Ion Channelsmentioning
confidence: 98%
“…8 It has been shown, however, that the conformation of gramicidin is environment sensitive and adopts different conformations with the change of membrane composition. For example, in detergent micelles, which mimic phospholipid bilayer of biomembranes, a head-to-head dimer formed from right-handed single strand ␤ 6.3 helices was proposed, 10,22,23 whereas in lipids composed of unsaturated fatty acids, gramicidin adopts interwound double-helical structure, 8,24 and in artificial lipid membrane it is observed that conformation of gramicidin is determined by its conformational behavior in the organic solvent where it was initially dissolved. 25 A limited number of vibrational absorption studies were undertaken on gramicidin, 9,24,26 -28 while most literature studies on gramicidin were carried out with electronic circular dichroism (ECD), NMR, and X-ray diffraction methods.…”
Section: Introductionmentioning
confidence: 98%
“…18 The rate of transition from the double-stranded helix to the single-stranded helical dimer depends on the lipid head group, acyl chain length, and unsaturated content. [19][20][21][22][23] Two models of this conformational change have been proposed. In the ''zipper'' mechanism, the intertwined chains unscrew in opposite directions by progressively shifting the antiparallel chains past each other.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] On the other hand, when apolar solvents are used, the double-helical conformation initially predominates. 15,19 This has been referred to as the ''solvent history'' of gramicidin A. In a phospholipid bilayer, this gramicidin double-stranded helix is a nonminimum energy conformation, [15][16][17][18][19] but conversion to the single-stranded helical dimer takes several hours if the polypeptide was initially dissolved in double-stranded helix-stabilizing solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation